STUDY OF DEVELOPMENT SENTANI LAKE'S WATER RESOURCE POTENTION IN KABUPATEN JAYAPURA PAPUA PROVINCE - WILLEM RUMERE (NIM 95006035), JAN
With condition of it's topography, geography and climatology, lake sentani have water resource potention than could be used for public interest. Lake Sentani locate in Sentani district, Kabupaten Jayapura, Papua Province that have capacity about 2,716 million m3, watershed area is about 571 Km2 with 11 Sub DAS as water resource sustainability potation that can be developed for needs in Domestic sector, Irrigation, Industrial, PLTM and can be separated from ecological conservation factor. Average of annual rain intensity about 1691,7 mm/year. Method that used for water sustainability analysis is NRECA Method. Average water sustainability forecast annually in lake sentani is 404,31 e/sec and annual water demand forecast for Domestic; 7,554.639 e/year flushing is 10 % from Qmin Inflow, Irrigation 12,28 I/dt/ha, Industrial 2,190 ml, PLTM; potential head is 35 m with Turbine capacity K-P/6 that can produce electrical power 12,052 kW. Land erosion velocity estimation is 4,643 ton/years that can cause sedimentation in Sentani lake with sedimentation velocity 0,243 ml/s.